Nutritional management of Cavia porcellus L. in the Andes of Colombia - Cardona Iglesias, Juan Leonardo (2021)
The Cavia porcellus L. systems implemented by small producers in Colombia have been slow to apply the processes of development and incorporation of feeding practices and technology in nutritional support. The objective of this study was to determine the feeding practices and technology in nutritional support implemented and projected in the C. porcellus L. systems by the producers. Four components were evaluated in 404 C. porcellus L.  units and 29 focus groups: demography, identification of the production unit, implemented feeding practices, technology in nutrition and feeding, and the C. porcellus L. producers' perspectives. A Pearson Chi-squared test, a Tukey’s T-test, and a Multiple Linear Regression were used to evaluate the differences between regions using SPSS software version 20. The average area of C. porcellus L. -producing units corresponded to 0.35 ha (Nariño) and 0.17 ha (Putumayo). The predominant food base was forage (67%) produced on the farm (83%). There were significant differences between regions, with a p < 0.05 in food base, forage cultivation area, forage conservation feeding practices, type of fertilization, and the group of animals supplemented. The use of technology such as feed based on kitchen waste and supplements was used by producers in the Putumayo region (p > 0.05) most frequently. Our data show that C. porcellus L. systems in the study area not only have a high potential in the diversity of the forage supplements that makes up the diets but also in the development and implementation of feeding practices and technology in nutrition and animal feeding.